2017
DOI: 10.1002/slct.201701133
|View full text |Cite
|
Sign up to set email alerts
|

2,6-(Diphenylmethyl)-Aryl-Substituted Neutral and Anionic Phosphates: Approaches to H-Bonded Dimeric Molecular Structures

Abstract: 2,6‐(Diphenylmethyl)‐4‐alkyl‐phenyl substituted phosphates, ArOP(O)(OH)2 (Ar=2,6‐CHPh2‐4‐R‐C6H2; R=Me (9), Et (10), iPr (11), and tBu (12)), were synthesized from the corresponding phenols. The single crystals of these compounds were obtained from their solutions of CH3CN or CH3COCH3. The molecular structures of these compounds, in the solid state, determined by single crystal X‐ray analysis reveal that they possess a hitherto unknown structural motif among monoorganophosphate esters viz., a dimeric hydrogen b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 112 publications
0
20
0
Order By: Relevance
“…The P–O bond length found in 4 is 1.478(2) Å, which is shorter compared with that of 5 (1.492(2) Å) presumably because of a H-bonding interaction with an imidazolium cation. 25 The P–P distance in 4 (2.1946(8) Å) is slightly longer than that observed in the metal carbonyl (Lewis acid) free phospha-Wittig–Horner reagent, (Mes*PH–P(O)(OEt) 2 ) (2.1854 Å). 26 …”
Section: Resultsmentioning
confidence: 89%
“…The P–O bond length found in 4 is 1.478(2) Å, which is shorter compared with that of 5 (1.492(2) Å) presumably because of a H-bonding interaction with an imidazolium cation. 25 The P–P distance in 4 (2.1946(8) Å) is slightly longer than that observed in the metal carbonyl (Lewis acid) free phospha-Wittig–Horner reagent, (Mes*PH–P(O)(OEt) 2 ) (2.1854 Å). 26 …”
Section: Resultsmentioning
confidence: 89%
“…6 Aggregation behaviour of para-substituted monoarylphosphates have been very well studied and the formation of H-bonded non-porous and porous 3-D framework structures was reported. [29][30][31][32] Recently Murugavel et al, 33 and we 34 have shown that phosphate monoesters, 2,6-(CHPh) 2 -4-R-C 6 H 2 O-P(O)(OH) 2 form solvent assisted dimeric molecular structures in the solidstate. The corresponding anionic phosphate monoesters derived from these bulky phosphate monoesters exhibit structural diversity in supramolecular organization based on counter cations 35 as well as modulation of the nuclearity of molecular Mg(II)phosphates.…”
Section: Introductionmentioning
confidence: 71%
“…The hydrogen bonding between the two phosphate motifs leads to the formation of an eight-membered P 2 O 4 H 2 ring similar to what had been observed in the ion pair with the triethylammonium cation. 26 The solution- and solid-state CP-MAS 31 P{ 1 H} NMR spectra of 10 shows single singlet resonances at δ = −4.6 and −3.9 ppm, respectively, suggesting the presence of only one type of phosphorus center in the molecule.…”
Section: Resultsmentioning
confidence: 98%
“…Although molecular phosphate monoesters mostly form polymeric structures in the solid state, 1725 we have recently reported the syntheses of several bulky aryl-substituted neutral and anionic phosphate monoesters ( 1 – 8 in Scheme 1), which exhibit H-bonded dimeric molecular structures analogous to those in carboxylic acids. 26 Through partial blockage of the H-bonding potential of the ArOP(O)(OH) 2 unit by using either a hydrogen-bonding acceptor solvent (such as acetone or acetonitrile) or a hydrogen-bonding donor as counter cation (such as triethylammonium), we were able to realize dimeric supramolecular structures (Scheme 1). Murugavel et al independently also reported the synthesis and molecular structures of 1 and 4 .…”
Section: Introductionmentioning
confidence: 99%